Analysis of the Impact of Traffic on the Construction of the Jl. Underpass. Gatot Subroto, Medan City - Panggabean, Ariful Fikri Efendi; Lubis, Marwan; Simbolon, Ronal H T (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
Medan City, as the capital of North Sumatra Province, is facing severe traffic jams at the Jalan Gatot Subroto-Jalan Gagak Hitam intersection due to the rapid growth of vehicles. To overcome this problem, the Medan City Government plans to build an underpass to separate traffic flows and increase road capacity. This research aims to analyze the impact of traffic during the construction phase, by grouping vehicles into motorbikes, light vehicles and heavy vehicles, which are then converted into passenger cars (SMP). Research shows that the existing traffic volume is 2813.8 pcu/hour towards Jalan Ringroad and 2620.5 pcu/hour towards Jalan Asrama, which exceeds the road capacity. During the construction phase, traffic volume dropped significantly to 637.6 pcu/hour and 635.5 pcu/hour, which shows more stable traffic flow. construction of underpasses can effectively reduce future congestion, but careful planning is required to minimize negative impacts during the construction period. It is hoped that these results can provide important input in transportation planning in Medan City.